PERANAN PENYULUH AGAMA ISLAM DALAM DAKWAH - Ilham Ilham (UIN Antasari Banjarmasin, 2019)
Islam is a religion of da'wah which obliges his followers to preach according to their capabilities. Islamic instructors are part of the implementation of da'wah (da'i) guiding religious life of the people and bearers of the development mission with a religious approach to society. That is why Islamic Religion Counselors play a very important and strategic role in creating a religious, prosperous and happy society. It plays a role as a leader in religious, social and state affairs for its targets, social change agents, and motivators, facilitators and even community development catalysts.